1. The Effect Of Moringa (Moringa olifera) Leaves Infusion On Hemoglobin Level Of Broiler Chicken (gallus-gallus domesticus) - Zuhrawati NA; Amiruddin Amiruddin; Yopi Mardian; Zuraidawati Zuraidawati; Nuzul Asmilia; Rusli Rusli; Triva Murtina Lubis (Jurnal Medika Veterinaria, 2019)
The research aimed to determine the effect of Moringa leaves infuse toward the haemoglobin levels of broiler chickens. This study used 21 broiler chickens which divided into three groups and each group consisting of 7 broiler chickens. The treatment group (P0) were given only mineral water (aquadest), the treatment group (P1) were given moringa leaves infuse with a concentration of 10 % and treatment group (P2) infusion were given moringa leaves with a concentration of 20 %. The given of Moringa leaves infuse was starting at seven days old of chickens and given for 28 days continously as a drinking water.  The chickens were feed by ad libitum during the research. After the treatment completion, a researcher carried out a blood sampling via the axillary vein.  Data were analyzed with ANOVA by Complete Random Design one way and Tukey test to determine a difference between the treatments of each group. The research results showed that ± SD haemoglobin (g / dl) in the group (P0) 7.71 ± 1.13, (P1) of 8.15 ± 1.95 and (P2) 10.8 ± 1.76. Statistical analysis showed the treatment effect (P 0.05) of the haemoglobin levels of broiler chickens. The Tukey test results of the treatment group (P0) were significantly different (P 0.05) with treatment group (P2), but not significantly different (P 0.05) with treatment group (P1). The treatment group (P2) were significantly different (P 0.05) with treatment group (P1). From the results of this research, it was concluded that infuse Moringa leaves can improve haemoglobin levels of broiler chicken.